Lakeshore Christmas - Wiggs, Susan (Wiggs, Susan. Lakeshore chronicles, 2009)
Prim librarian Maureen Davenport lives for Christmas--and there's nothing more magical than Christmas on Willow Lake. Finally getting her chance to direct Avalon's annual holiday pageant, she's determined to make it truly spectacular. But it might just require one of those Christmas miracles she's always read about if her co-director-- recovering former child star Eddie Haven--has his way. Is he trying to sabotage the performance to spite her? Or is she trying too hard to fit the show into her storybook-perfect notion of Christmas?